Laboratory patterns related to dengue fatality: A literature review (Research, Society and Development, 2024)
Introduction: Dengue, the main arbovirus in the world, although manifesting as a mild viral illness in most patients, has been a cause for concern due to the increasing number of deaths. The analysis of laboratory tests is one of the main tools to predict the patient's poor evolution, since some hematological patterns are altered from the beginning. Objective: Therefore, the objective was to analyze what these laboratory alterations are in patients fatal from dengue. Methodology: The descriptors "dengue", "blood tests", "mortality", "severe dengue" were searched in the LILACS, PubMED and SciELO databases, using the boolean term AND. A total of 1338 studies were found, of which 13 were selected as a sample, after selection based on inclusion and exclusion criteria previously defined by the authors. The main alterations related to dengue mortality were elevation of liver enzymes, bilirubin, creatinine, urea, and leukocytes, as well as anemia with increased hematocrit and a sharp drop in platelet count. Final considerations: Laboratory values should be analyzed together, used as a tool to predict dengue severity, avoiding progression to a poor prognosis and fatality.